PERAN PENDIDIKAN ISLAM DALAM PERUBAHAN SOSIAL BUDAYA DI MASYARAKAT - Riwansah, Wiro; Sutrisno, Ihsyan; Ubabuddin, Ubabuddin (ILJ: Islamic Learning Journal, 2024)
The purpose of this article is to discuss the role of Islamic education in socio-cultural changes in society. The research is a literature research, with documentary data collection methods, and analysis using content analysis. The results of the research state that every human being who lives in society, during his life is bound to experience changes. Changes in society can be about social values, social norms, patterns of organizational behavior, the composition of social institutions, layers in society, power and authority, social interaction and so on. Because of the breadth of areas where these changes can occur, when someone wants to make research it is necessary to first determine firmly, what changes are intended so that in conducting research already has a clear and definite direction. Socio-cultural change is a symptom of changing social structures and cultural patterns in a society. Socio-cultural change is a common symptom that occurs throughout time in every society. These changes occur in accordance with the nature and nature of humans who always want to make changes.